Acute effects of knee wraps/sleeve on kinetics, kinematics and muscle forces during the barbell back squat - Sinclair, J.; Mann, J.; Weston, G.; Poulsen, N.; Edmundson, C. J.; Bentley, I.; Stone, M. (Sport Sciences for Health, 2020)
Purpose: The aim of the current investigation was to comparatively examine the effects of knee wraps/sleeves on kinetics, three-dimensional kinematics and muscle forces during the barbell back squat. Methods: Fifteen male lifters completed squats at 70% of their 1 repetition maximum, in four different conditions (nothing, competition knee wrap, training knee wrap and knee sleeve). Three-dimensional kinematics were measured using an eight-camera motion analysis system, ground reaction forces using a force platform and muscle forces using musculoskeletal modelling techniques. Differences between conditions were examined using one-way repeated measures ANOVA. Results: The results showed that the integral of the quadriceps (nothing = 58.30, competition = 51.87 and training wrap = 53.33 N/kg s), hamstring (nothing = 39.01, competition = 35.61 and training wrap = 33.97 N/kg s), gluteus maximus (nothing = 24.29, competition = 22.22 and training wrap = 21.03 N/kg s), gastrocnemius (nothing = 7.25, competition = 5.97 and training wrap = 6.39 N/kg s) and soleus muscles (nothing = 15.49, competition = 12.75 and training wrap = 13.64 N/kg s) during the ascent phase was significantly greater in the nothing condition compared to both knee wraps. In addition, whilst knee wraps and knee sleeves significantly improved perceived knee stability, perceived comfort was significantly reduced in the knee wraps and improved in the knee sleeve. Conclusions: Taking into account the reduced muscle kinetics, knee wraps may diminish lower extremity muscle development. Therefore, knee sleeves may be more efficacious for athletes who regularly utilise the back squat for their training goals, although further longitudinal analyses are required before this can be fully established.